Tipologi Inovasi Pelayanan Sektor Publik: Klampid New Generation (KNG) Pada Kota Surabaya - Indah Nur Septiani; Indira Arundinasari (UIR Press, 2023)
Population Administration is a series of structuring and controlling activities in the publication of documents and Population Data through Population Registration, Civil Registration, management of Population Administration information and utilization of the results for public services and development of other sectors. To improve the quality of service at Dispendukcapil Surabaya launched an innovation called Klampid New Generation (KNG). This research aims to explain how Population Administration service innovations carried out by Dispendukcapil through Klampid New Generation cover six important aspects. This type of research is descriptive with a qualitative approach. Interviews, observation and documentation are the techniques used in collecting research data. The research focus includes new or improved services, process innovation, administrative innovation, system innovation, conceptual innovation, and radical change of rationale. This research data analysis uses interactive data analysis. The research results show that the City of Surabaya has succeeded in creating public service innovation through Klampid New Generation. Klampid New Generation has had a positive impact on Population Administration services in the City of Surabaya, although there are still shortcomings in it.